EDUKASI PANGAN SUMBER ANTIOKSIDAN DAN OPTIMALISASI SKINCARE UNTUK PENCEGAHAN PENUAAN DINI - Septiani, Septiani; Nurohmi, Susi; Widyan Aisya, Rizki; Tri Sukoharjanti, Bintari; Inas Salsabila, Zumaila; Hartanto, Fitria Syarifa (Jurnal Abdi Insani, 2024)
Young women are at risk of experiencing premature aging. Early aging can be influenced by various factors such as an unhealthy diet, irregular sleep patterns, lack of hydration, and exposure to free radicals. In addition, the selection of skincare products can also affect skin health. Pimpinan Ranting Nasyiatul Aisyiyah Pasuruhan is experiencing various skin health issues such as dry skin, the appearance of fine wrinkles, and dark spots on the face. This community service aims to provide education on food sources of antioxidants and the optimization of skincare to prevent premature aging. The methods of activities include preparation, implementation, and evaluation. The activities are divided into two sessions: the first session focuses on nutritious food sources of antioxidants and introduces the development of a product in the form of an anti-aging salad booster that is high in antioxidants. The second session is about optimizing skincare to prevent premature aging. The result of this activity is a change in nutritional knowledge values based on the average scores before and after the counseling, which also shows a significant difference. The results of the statistical test indicate that there is an increase in nutrition knowledge from 74.5 to 83.1 (p-value<0.05). This finding suggests that nutrition education utilizing technology can help enhance nutrition knowledge and antioxidant awareness among training participants. In conclusion, there has been an increase in the knowledge of PRNA Pasuruhan members about food sources of antioxidants and the optimization of skincare to prevent premature aging.